Iowa Birdline update, May 30, 1994 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1994)
Email for the Iowa Birdline update for May 30, 1994. Highlights include a Purple Gallinule and a Whimbrel. Epson - sheet feed/flatbed